R12 Metamorphosis Reproduction (Metamorep) Theory In Creation Of The Universe With Dynic Paradigm And Economic Covid Era - R Mochamad Aziz (Proceeding of International Conference on Information Science and Technology Innovation (ICoSTEC), 2022)
The purpose of this study is to analyze the creation of the universe with the Dynic Paradigm according to the R12 Metamorphosis Reproduction (Metamorep) Theory in the 6 stages of the Covid economic era. The theory of R12 metamorphosis is based on the formula R12 and the Metamorphosis pattern. R12 is the Roikhan-12 formula that develops the Initial Edge Concept. The Metamorphosis Pattern is found in the changes in the Butterfly from the beginning. The Dynic Paradigm refers to the content of the scriptures according to truth and facts. This research was conducted in a desk study by collecting sources from scriptures, journals, books, and electronic media. The methodology used is Reflective Qualitative. The method used is metaphor and similarity. The result obtained is the Theory R12 Metamorphosis in the creation of the universe consists of 6 stages. This stage is a combination of the butterfly life cycle plus the creature's breeding cycle. It starts with 1 dot like an egg which contains high-density matter. Then there was a separation which was called the Early Edge Concept. Similar to this concept is the meaning of the Quran Surah Hid 11.114 which is interpreted as a separation from 1 solid dot into 2 parts, namely the edge of the universe's matter has 2 parts, and at the beginning of the universe's matter, there is 1 part in the caterpillar metaphor. Followed by the transformation into a Nebula with smoke covering the galaxy with the metaphor of a cocoon with the reflexivity of the universe praying. The last stage of Metamorphosis is the Butterfly which is represented in the form of the universe starting to develop at the beginning of its perfection. Two additional stages are before the reproductive period with the maturity level of the young universe. The last is the reproduction phase of the universe with a more mature maturity. The Dynic Paradigm is a solution for the development of the theory of the creation of the universe that combines existing theories with the contents of the holy book of the Covid economic era.